Clinical outcomes of patients with a single hepatocellular carcinoma less than 5 cm treated with transarterial chemoembolization - Baek, Min Young; Yoo, Jeong-Ju; Jeong, Soung Won; Jang, Jae Young; Kim, Yong Kwon; Jeong, Shin Ok; Lee, Sae Hwan; Kim, Sang Gyune; Cha, Sang-Woo; Kim, Young Seok; Cho, Young Deok; Kim, Hong Soo; et al. (The Korean journal of internal medicine, 2019)
Transarterial chemoembolization (TACE) is performed for single hepatocellular carcinoma (HCC) that are not eligible for surgery or ablation therapy. We investigated the clinical outcomes of patients with a single HCC ≤ 5 cm treated with TACE. This study analyzed 175 consecutive patients who underwent TACE as an initial treatment for single HCC ≤ 5 cm. Predictive factors for complete response (CR), recurrence after CR, and overall survival (OS) were evaluated. Total 119 patients (68%) achieved CR after TACE. Tumor size < 3 cm and hepatitis B virus infection were significant predictors of CR (p < 0.05). Recurrent HCC was detected in 73 patients (61.3%) after CR. Age > 65 years and absence of liver cirrhosis were predictive factors for non-recurrence after CR (p < 0.05). The OS for all patients was 80.7 ± 5.6 months, and the 1-, 3-, and 5-year OS rates were 88.1%, 64.8%, and 49.9%, respectively. In multivariate analysis for OS, CR (hazard ratio [HR], 0.467; 95% confidence interval [CI], 0.292 to 0.747) and Child class A (HR, 0.390; 95% CI, 0.243 to 0.626) were significant factors. The OS for the CR and Child class A group were 92 and 93.6 months, respectively, and that of the non-CR and Child B, C group were 53.3 and 50.7 months, respectively (p < 0.001). TACE can be a valid treatment in patients with a single HCC ≤ 5 cm not suitable for curative treatment, especially in patients with Child class A and CR after TACE.